Stability Analysis of a T-S based Intra-Specific Predator-Prey Competition Model with Fuzzy Impulsive Control - Kaladhar, K.; Singh, Khushbu (Journal of Applied Nonlinear Dynamics, 2026)
Predator-prey system, which has been widely employed in recent years, offers a suitable mathematical model for presenting the relationship among prey and predators. We will look at a non-linear differential system in this paper. We created two intra-species predator-prey model, one for prey and another for predator, based on the Lotka-Volterra predator-prey model. The Takagi-Sugeno (T-S) impulsive control model and the fuzzy impulsive control model were used to explore the stability of the Lotka-Volterra predator-prey system. Numerical simulation provides the global stabilities and the fuzzy solution.